Changes in nutritional status of children who lived in temporary shelters in Bhaktapur municipality after the 2015 Nepal earthquake - Dhoubhadel, BG; Raya, GB; Shrestha, D; Shrestha, RK; Dhungel, Y; Suzuki, M; Yasunami, M; Smith, C; Ariyoshi, K; Ariyoshi, K; Ariyoshi, K; Parry, CM (BioMed Central, 2020)
Background The nutritional status of children may deteriorate after natural disasters such as earthquakes. A 7.8 Richter scale earthquake struck Nepal in 2015 that affected 1.1 million children. Children whose homes were destroyed and had to live in temporary shelters were at risk of malnutrition. With the support of Nagasaki University School of Tropical Medicine and Global Health (TMGH) and Siddhi Memorial Hospital (SMH), we conducted a nutritional survey of under-5 children living in temporary shelters in Bhaktapur Municipality in 2015 immediately after the earthquake and a follow-up survey in 2017. Results We found 591 under-5 children living in 22 temporary shelters in 2015. A total of 285 children were followed up and re-assessed in 2017. In a paired analysis (n = 285), the prevalence of underweight children increased from 10.9% in 2015 to 14.0% in 2017 (P < 0.001), stunting increased from 26.7 to 31.9% (P = 0.07), and wasting decreased from 4.2 to 2.5% (P = 0.19). Conclusions Children who lived in temporary shelters after the 2015 Nepal earthquake might be at increased risk of a deterioration in nutritional status.